EFL Student- Teachers' Perception in the Culture of Thinking (Journal of the College of Education for Women, 2022)
Many studies have recommended implying the skills and strategies of creative thinking, critical thinking, and reflective thinking in EFLT curriculum to overcome EFL teaching-learning process difficulties. It is really necessary to make EFL teachers aware of the importance of cultural thinking and have a high perception of its forces. Culture of thinking consists of eight cultural forces in every learning situation; it helps to shape the group's cultural dynamic. These forces are expectations, language, time, modeling, opportunities, routines, interactions, and environment. This study aims to investigate EFL student-teachers’ perceptions of cultural thinking. The participants are selected randomly from the fourth-stage students at the Department of English Language-College of Education for Women-University of Baghdad. The total population is (105), while the participants are (87) student-teachers. Ritchhart’s (2015) Eight-Cultural-Forces Scale was adopted as a study tool, and its face validity and reliability have been ascertained. It has been concluded that the student-teachers perceive the culture of thinking moderately despite their training program lack any sort of cultural thinking forces.